De la teoría de sistemas a la unidad teleológica del viviente - Ferrer, Urbano (Logos. Anales del Seminario de Metafísica, 2007)
The article examines the notion of open system as suitable for giving an account of dynamism of living being. However difficulties come by trying to incorporate the finality to the system, since it´s fixed as a state from outside or is established in the improper terms of autoproductivity and neguentropye. That leads to explain the final cause in interaction with the other intrinsecal causes, in as much they remain incomplete without her. Whith the passage to human living the linear scheme means-end should be replaced by the expressions which reveal an end in itself.